Cooperative catalysis-enabled C–N bond cleavage of biaryl lactams with activated isocyanides. Issue 43 (9th May 2022) - Wang, Wen-Tao; Zhang, Sen; Tao, Ling-Fei; Pan, Zi-Qi; Qian, Linghui; Liao, Jia-Yu
Abstract : An unprecedented highly enantioselective reaction of biaryl lactams with activated isocyanides has been realized by merging organocatalysis with metal catalysis. Abstract : The catalytic reaction of biaryl lactams with activated isocyanides is reported for the first time. By employing a cooperative catalytic system, oxazole-containing axially chiral biaryl anilines were obtained in high yields with excellent enantioselectivities. The key to the success lies in the atroposelective amide C–N bond cleavage with activated isocyanides.